PENGARUH ETIKA AUDITOR, KOMPETENSI, TIME BUDGET PRESSURE DAN FEE AUDIT TERHADAP KUALITAS AUDIT DENGAN FEE AUDIT SEBAGAI VARIABEL MODERASI (Studi Pada Kantor Akuntan Publik Di DKI Jakarta) - Agung Suprianto (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The purpose of this study was to determine the effect of the influence of ethics of auditor, competence, audit fee and time budget pressure on audit quality with audit fee as a moderation variable (study in a public accounting firm in Jakarta). This study was designed using a descriptive statistical approach to test hypotheses that are not causal. The population for testing this research hypothesis is all auditors who work in KAP in Jakarta. Meanwhile, the determination of the sample in this study was carried out in convenience sampling and set as many as 63 respondents. Data collection techniques were carried out by distributing questionnaires to auditors in Jakarta. Data analysis method in this research uses multiple regression. The results showed that ethics of auditor and time budget pressure had an effect on audit quality, competence and auditing fees doesn’t has effect on audit quality. Audit fees does not strengthen the influence of etnics of auditor on audit quality, and audit fees has strengthened the influence of competence on audit quality, meanwhile audit fee has not weakness the influence of tie budget pressure on audit quality.